Fetal fraction‐based risk algorithm for non‐invasive prenatal testing: screening for trisomies 13 and 18 and triploidy in women with low cell‐free fetal DNA. (26th November 2018) - McKanna, T.; Ryan, A.; Krinshpun, S.; Kareht, S.; Marchand, K.; Grabarits, C.; Ali, M.; McElheny, A.; Gardiner, K.; LeChien, K.; Hsu, M.; Saltzman, D.; et al.
ABSTRACT: Objective: To identify pregnancies at increased risk for trisomy 13, trisomy 18 or triploidy attributable to low fetal fraction (FF). Methods: A FF‐based risk (FFBR) model was built using data from more than 165 000 singleton pregnancies referred for single‐nucleotide polymorphism (SNP)‐based non‐invasive prenatal testing (NIPT). Based on maternal weight and gestational age (GA), FF distributions for normal, trisomy 13, trisomy 18 and triploid pregnancies were constructed and used to adjust prior risks for these abnormalities. A risk cut‐off of ≥ 1% was chosen to define pregnancies at high risk for trisomy 13, trisomy 18 or triploidy (high FFBR score). The model was evaluated on an independent blinded set of pregnancies for which SNP‐based NIPT did not return a result, and for which pregnancy outcome information was gathered retrospectively. Results: The evaluation cohort comprised 1148 cases, of which approximately half received a high FFBR score. Compared with rates expected based on maternal age (MA) and GA, cases with a high FFBR score had a significantly increased rate of trisomy 13, trisomy 18 or triploidy combined (5.7% vs 0.7%; P  < 0.001) and also of unexplained pregnancy loss (14.7% vs 10.4%; P  < 0.001). For cases that did not receive a high FFBR score, the incidence of a chromosomal abnormality or pregnancy loss was not significantly different from that expected based on MA and GA. In this study cohort, the sensitivity of the FFBR model for detection of trisomy 13, trisomy 18 or triploidy was 91.4% (95% CI, 76.9–98.2%) with a positive predictive value of 5.7% (32/564; 95% CI, 3.9–7.9%). Conclusions: For pregnancies with a FF too low to receive a result on standard NIPT, the FFBR algorithm identified a subset of cases at increased risk for trisomy 13, trisomy 18 or triploidy. For the remainder of cases, the risk of a fetal chromosomal abnormality was unchanged from that expected based on MA and GA. © 2018 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.